(3GdEcdjd hGdJGL aj JPjjd caGjI GdeMJGLs - (3eMeO Hf GdWjH Hf YHO GdSdGe GdMSfj GdbGOQj , CHh YHO Gddg,J (B1187 (3g` s; (3CMeO HGHG Hf CMeO Hf CMeO Hf YeQ GdJcQhQj GdJfHcJj,J (B1036 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdP bVi Ydi cd eNdhb HGdbVGA CeG HYO ajbhd GdYHO GdabjQ GdePfH eMeO Hf GdWjH HgPG GdLRA Ef TGA Gddg JPjjd caGjI GdeMJGL s
(3BNQgG (B:s
(3jfJgi HJQLeI (B" (3BefI GdHSJhfjI (B" (3ef HGH JQGLe GdfSGA hCNQ eG ajg (B: (3hCYhP Hg JYGdi ef Yde dG jfaY agh Gdehdi GdLdjd hgh MSHi hfYe Gdhcjd s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B102s
Keywords: (3GdJGQjNs